ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN DERMATITIS KONTAK PADA PEDAGANG IKAN DI PASAR SENTRAL KOTA SORONG PAPUA BARAT - Putri Yanti; Asna Ampang Allo (Jurnal Kesehatan dan Kedokteran, 2022)
Skin disease is one of the most common occupational diseases. It has been reported that hand dermatitis and fungal infections can be caused by prolonged exposure to water that causes itchy skin. The purpose of this study was to analyze the factors associated with contact dermatitis. The independent variables in this study were age, working period, and personal hygiene, the dependent variable in this study was dermatitis. This type of research uses a cross sectional study approach, the sample size in this study is 73 peoples. The results of the chi-square test showed that age, working period and personal hygiene were associated with dermatitis. It is expected for fishmonger to maintain cleanliness by washing hands and using soap and water flow, taking shower after doing activity in market.